2009
DOI: 10.14295/ba.v2.0.52
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Used Coffee Grounds on Larval Mortality of Aedes aegypti L. (Diptera: Culicidae): Suspension Concentration and Age versus Efficacy

Abstract: Efeito da Borra de Café na Mortalidade Larval de Aedes aegypti L. (Diptera: Culicidae): Concentração eIdade da Suspensão versus Eficácia RESUMO -Em estudo anterior, a borra do café afetou o desenvolvimento larval de Aedes aegypti L. No presente trabalho, foi analisada a duração do efeito na mortalidade larval, de suspensões aquosas de borra do café, nas concentrações 75, 150, 250 e 300 mg/ml. A mortalidade larval nos criadouros experimentais foi acompanhada diariamente: a concentração 300 mg/ml foi a mais efic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…This action was cited by Guirado et al (2009) as one of the defense mechanisms of vectors and a common condition observed in resistant populations found in the national territory.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This action was cited by Guirado et al (2009) as one of the defense mechanisms of vectors and a common condition observed in resistant populations found in the national territory.…”
Section: Resultsmentioning
confidence: 99%
“…A current form of control is fogging insecticides such as organophosphate and pyrethroid, but their continuous use has resulted in resistance of populations (Guirado and Bicudo 2009) and exposure of operators (Vilela et al 2010) to the compounds. These effects have been reported in Latin American countries, decreasing the effectiveness of this strategy in mosquito control (Rodríguez and Fernández 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the efficacy of the used coffee grounds as larvicide, the literature shows very different results. Guirado and Bicudo (2007) recorded a complete mortality of Ae. aegypti larvae but using a very high quantity of dry UCG (300 mg/ml) while Laranja et al (2003) completely killed the larvae of the same species using only 50 mg/ml.…”
Section: Discussionmentioning
confidence: 99%
“…The internet has, surely, contributed to the wide circulation of information regarding possible alternative and biological methods for fighting mosquitoes. This led to the testing of different substances and materials including metallic copper (Della Torre et al, 1993), coffee grounds (Dieng et al, 2018;Ellias et al, 2015;Guirado and Bicudo, 2007;Laranja et al, 2003;Wiwanitkit, 2018) and tea extracts (Dieng et al, 2016). One advantage of the use of alternative insecticides would be to overcome the onset of resistance phenomena (Dieng et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Potential insecticidal activity of coffee was tested on leaf-cutting ant (Atta sexdens rubropilosa) with negative results (Miyashira et al, 2011) and on mosquito (Aedes aegypti) with positive results (Guirado and Bicudo, 2007;Laranja et al, 2003).…”
mentioning
confidence: 99%